Preliminary results with intravaginal culture of oocytes-intracytoplasmatic sperm injection (INVO-ICSI) at Procrear Fertility Center - Hilario, Roly (2014)
Objectives: To determine preliminary results of pregnancy rate per transfer in patients undergoing intravaginal oocyte culture-intracytoplasmatic sperm injection (INVO-ICSI) at a fertility center. Design: Descriptive, series of cases study. Setting: Procrear Fertility Center, Lima, Peru. Participants: Couples with infertility treatment. Interventions: Thirteen INVO–ICVSI performed in 12 patients from December 2011 through July 2013 were reviewed. SPSS program was used. Main outcome measures: Pregnancy rate. Results: Women’s average age was 35.38 years ± 3.35 and were seeking pregnancy 2.25 years ± 1.88 average. Infertility was due to male factor in 46.2% and to female factor in 53.2%. Embryo transfer was done in all cycles and 5 pregnancies were obtained (38.46% of cycles), 3 singleton (60%) and 2 double pregnancy (40%). Conclusions: INVO-ICSI fertilization rate was comparable and aceptable against other fertilization techniques.